2-14=-8t+4t

Simple and best practice solution for 2-14=-8t+4t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-14=-8t+4t equation:


Simplifying
2 + -14 = -8t + 4t

Combine like terms: 2 + -14 = -12
-12 = -8t + 4t

Combine like terms: -8t + 4t = -4t
-12 = -4t

Solving
-12 = -4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '4t' to each side of the equation.
-12 + 4t = -4t + 4t

Combine like terms: -4t + 4t = 0
-12 + 4t = 0

Add '12' to each side of the equation.
-12 + 12 + 4t = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 4t = 0 + 12
4t = 0 + 12

Combine like terms: 0 + 12 = 12
4t = 12

Divide each side by '4'.
t = 3

Simplifying
t = 3

See similar equations:

| 5x^2+11x-66=0 | | 5(y*2-4)=-21y | | 6x^2+x=2 | | 6t*2=7 | | s*2-9=0 | | 4(6x-9)=3(12x-8) | | 6z-5=7z-7 | | 6(y+1)-5=7 | | 7-z=3+z+4-2z | | 2u=u-6 | | 8x-4=(2x+1) | | 2x^2+3y^2-30=0 | | 2w+3=7w+13 | | 4y^2+11y+7=5 | | 5y-8=3y+5 | | 4x-3x-7=6x | | 22-3(c-1)=-3c+25 | | 4k^2+6k-1=0 | | 4x-32=2x | | 2(n-1)=8n-3 | | 6x-1=25 | | 2y-x=8 | | -13(x+1)=-13x-13 | | 9x^2+49x+64=0 | | -5(a+1)=4(a+10) | | 4x-4=4x | | 2x^2+18x+28=0 | | -20x=-4x-6x | | 4*u=28 | | x=15-2x | | 2x^2-12x+19=0 | | y=4x^2+x-5 |

Equations solver categories